Latin America and the Caribbean as Tailwinds Recede : In Search of Higher Growth, LAC Semiannual Report, April 2013 - de la Torre, Augusto; Pienknagura, Samuel; Levy Yeyati, Eduardo (World Bank, Washington, DC, 2013)
This semiannual report — a product of the Office of the Chief Economist for Latin America and the Caribbean Region of the World Bank — examines the short and medium-term challenges for Latin America and the Caribbean (LAC) as the external factors that were instrumental in the region’s recent performance recede. Chapter 1 gives an overview of the global economy and its implications for the short- and medium-term prospects of the LAC region. Chapter 2 provides a detailed analysis of the general patterns of domestic demand and supply observed in LAC over the last decade. In particular we document the steady increase in LAC’s domestic demand, especially its investment component, as a share of GDP over the 2000s. Moreover, we show that the rise of domestic demand has occurred in tandem with an expansion of the services sector. We assess what are the pitfalls and challenges for LAC’s growth pattern in a less benign global environment.